Early changes in cell‐free DNA levels in newly transplanted heart transplant patients. (11th December 2019) - Zangwill, Steven D.; Kindel, Steven J.; Ragalie, William S.; North, Paula E.; Pollow, Alyssa; Hidestrand, Mats; Tomita‐Mitchell, Aoy; Stamm, Karl D.; Mitchell, Michael E.
Abstract: Heart transplantation is a well‐established therapy for end‐stage heart failure in children and young adults. The highest risk of graft loss occurs in the first 60 days post‐transplant. Donor fraction of cell‐free DNA is a highly sensitive marker of graft injury. Changes in cell‐free DNA levels have not previously been studied in depth in patients early after heart transplant. A prospective study was conducted among heart transplant recipients at a single pediatric heart center. Blood samples were collected from children and young adult transplant patients at three time points within 10 days of transplantation. DF and total cell‐free DNA levels were measured using a targeted method (myTAIHEART ). In 17 patients with serial post‐transplant samples, DF peaks in the first 2 days after transplant (3.5%, [1.9‐10]%) and then declines toward baseline (0.27%, [0.19‐0.52]%) by 6‐9 days. There were 4 deaths in the first year among the 10 patients with complete sample sets, and 3 out of 4 who died had a late rise or blunted decline in donor fraction. Patients who died trended toward an elevated total cell‐free DNA at 1 week (41.5, [34‐65] vs 13.6, [6.2‐22] P = .07). Donor fraction peaks early after heart transplant and then declines toward baseline. Patients without sustained decline in donor fraction and/or elevated total cell‐free DNA at 1 week may have worse outcomes.